INFLUENCE OF ORGANISATIONAL STAFF CAPACITY ON THE IMPLEMENTATION OF ELECTRONIC PROJECT MONITORING INFORMATION SYSTEM IN PUBLIC TERTIARY INSTITUTIONS IN KENYA - Mburugu, Kirema Nkanata; Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge. (European Scientific Journal, ESJ, 2015)
This article highlights on the urgent need for staff training on new technologies, provision of adequate ICT infrastructure and staff attitudinal change trainings for effective implementation of new electronic based systems. The article is based on an empirical study carried out in Public Tertiary Institutions in Kenya to the extent of the implementation of Electronic Project Monitoring Information System (e-ProMIS) in the institution. The objective of the study was to establish the organizational internal context on the implementation of e-ProMIS, focusing on influence of staff capacity. The study adopted pragmatic paradigm using mixed mode approach and cross sectional research design with a target population of 460 members of staff from 35 public tertiary institutions in Kenya. A sample of 210 staff was selected using stratified and simple random sampling techniques. Data was collected using questionnaire with both open and structured items with Likert-type interval scale anchored on a five point scale. Descriptive statistics were computed for all variables using arithmetic mean and standard deviation. Statistical tools used for inferential statistic were Pearson’s Product Moment Correlation (r), simple regression, multiple regression and stepwise regression (R2). F-tests were used to test hypotheses in the study. The results revealed that staff capacity had a statistically significant influence on implementation of e-ProMIS. The study confirmed the relevance of Diffusion of Innovation Theory, Theory of Structuration and Technology Acceptance Model in studying implementation of electronic based systems. The study highlights the need for staff training on new technologies, provision of adequate ICT infrastructure and staff attitudinal change trainings for effective implementation of new electronic based systems. The study offers direction to policy makers and practitioners. The study recommends further research to be conducted to establish the influence of monitoring and evaluation on implementation of e-government systems. Other e-government systems like e-procurement and e-tax also need to be studied.